2017
DOI: 10.1038/ijo.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

l-phenylalanine modulates gut hormone release and glucose tolerance, and suppresses food intake through the calcium-sensing receptor in rodents

Abstract: Objective:High-protein diets (HPDs) are associated with greater satiety and weight loss than diets rich in other macronutrients. The exact mechanisms by which HPDs exert their effects are unclear. However, evidence suggests that the sensing of amino acids produced as a result of protein digestion may have a role in appetite regulation and satiety. We investigated the effects of l-phenylalanine (L-Phe) on food intake and glucose homeostasis in rodents.Methods:We investigated the effects of the aromatic amino-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 49 publications
3
84
1
Order By: Relevance
“…Similar results have been reported in previous studies, several amino acids such as l-Phe, l-Gln, and l-Arg induce gut hormone secretion in the murine small intestine, and this effect is enhanced by another CaSR agonist NPS R568 and is inhibited by NPS 2143 (Mace et al, 2012). In addition, Alamshah et al (2017) demonstrated that ileal administration of l-Phe stimulated GLP-1 and PYY release and reduced food intake in rats. However, the addition of CaSR inhibitor NPS 2143 attenuated the hormone release and anorectic effect induced by l-Phe in rats.…”
Section: Misukonissupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been reported in previous studies, several amino acids such as l-Phe, l-Gln, and l-Arg induce gut hormone secretion in the murine small intestine, and this effect is enhanced by another CaSR agonist NPS R568 and is inhibited by NPS 2143 (Mace et al, 2012). In addition, Alamshah et al (2017) demonstrated that ileal administration of l-Phe stimulated GLP-1 and PYY release and reduced food intake in rats. However, the addition of CaSR inhibitor NPS 2143 attenuated the hormone release and anorectic effect induced by l-Phe in rats.…”
Section: Misukonissupporting
confidence: 91%
“…In addition, Alamshah et al. () demonstrated that ileal administration of l ‐Phe stimulated GLP‐1 and PYY release and reduced food intake in rats. However, the addition of CaSR inhibitor NPS 2143 attenuated the hormone release and anorectic effect induced by l ‐Phe in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo intestinal perfusion demonstrates that the calcium concentration of the environment is essential for robust amino acid-induced GLP-1 secretion [8], which is thought to act via the synergistic stimulation of the calcium-sensing receptor by both calcium and amino acids [10,30]. It has also been demonstrated more recently that the calcium-sensing receptor mediates the effects of amino acids on gut hormone secretion, appetite and food intake in rodents, in vivo [11]. The present study is the first to demonstrate that ingestion of milk minerals rich in calcium further increases whey protein-induced postprandial GLP-1 secretion in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) by which dietary protein stimulates GLP-1 availability is thought to involve direct stimulation by amino acids of the calcium-sensing receptor expressed on L-cells in the intestine [8]. Importantly, it has now been shown across in vitro [9,10], ex vivo [8] and in vivo rodent models [11] that the calcium-sensing receptor regulates gut hormone release and is responsive to physiologically relevant extracellular calcium and amino acid concentrations across fasting to postprandial concentration range. However, to date, no study has demonstrated the synergistic effect of protein and calcium ingestion on GLP-1 availability in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Obvious candidate receptors include the other amino acid‐sensing receptors belonging to class C GPCRs such as CaSR and T1R1‐T1R3, which show overlapping tissue expression and L‐amino acid preferences with GPRC6A . In fact, CaSR has recently been demonstrated to mediate the effects of L‐phenylalanine on gut hormone release, which proves that this receptor is capable of inducing GLP‐1 secretion …”
Section: Suggested Physiological Functions Of Gprc6amentioning
confidence: 99%